Pemanfaatan Perpustakaan Digital untuk Memperkuat Transformasi Budaya Gotong Royong di Indonesia - Darmawan, Wawan; Wiryany, Detya; Agung Riyaldi, Muhammad (Media Informasi, 2025)
The development of information technology has transformed the social landscape, posing challenges to the continuity of gotong royong in Indonesia. Amid modernization often associated with individualism, traditional physical gotong-royong practices appear to be weakening, yet new forms of collective collaboration are emerging in the digital sphere. This study examines how digital libraries can function as socio-technical infrastructures to facilitate and strengthen the transformation of gotong-royong culture. Using a qualitative approach through literature review and case study analysis, it explores collaborative mechanisms on digital platforms. The findings show that digital libraries hold significant potential to evolve from mere information repositories into arenas of social interaction. Through participatory features, they can foster two forms of gotong royong: () digital kerja bakti (collective work), where communities build shared knowledge assets, as exemplified by the Sobat Budaya platform; and 2) digital tolong-menolong (reciprocal help), where individuals exchange knowledge and recommendations, as seen in the iJateng application. However, realizing this potential faces major challenges related to unequal access to technology and digital literacy. This research reconceptualizes digital libraries as active facilitators in revitalizing gotong royong as vital social capital in Indonesia’s digital era.